Cytomegalovirus Infection: Mouse Model. (25th July 2018) - Brizić, Ilija; Lisnić, Berislav; Brune, Wolfram; Hengel, Hartmut; Jonjić, Stipan
Abstract: This unit describes procedures for infecting newborn and adult mice with murine cytomegalovirus (MCMV). Methods are included for propagating MCMV in cell cultures and for preparing a more virulent form of MCMV from salivary glands of infected mice. A plaque assay is provided for determining MCMV titers of infected tissues or virus stocks. Also, a method is described for preparing the murine embryonic fibroblasts used for propagating MCMV and for the plaque assay. © 2018 by John Wiley & Sons, Inc.